PHYSICO-CHEMICAL PROPERTIES AND INDICES OF CHEMICAL AND MICROBIOLOGICAL SAFETY FOR ENZYME HYDROLYSATES OF FEATHER WASTE - Asyakina L.K.; Dolganuk V.F.; Milentieva I.S.; Noskova S.Y.; Babich O.O. (Техника и технология пищевых производств)
Full-fledged provision of animals, including poultry, with high-protein feed is necessary for the production of livestock products of such volumes that would ensure the country's food security. One of the ways to solve this problem is the use of raw materials for the recovery of useful components from the waste of the poultry processing industry. The right method chosen for utilization of such waste will ensure the production of components used for further enrichment of feed and mixed fodders. In the course of our research, enzymatic hydrolysates from wastes of evisceration of chickens of different breeds have been obtained using a multienzyme composition selected as a result of studying the peptide and amino acid composition of evisceration waste. The multienzyme composition included strains of microorganisms: Bacillus endophyticus 2102, Bacillus safensis sp., Bacillus pumilus SAFR032, Bacillus licheniformis B-2986, Streptomycesparvus sp. In the ratio 1: 1: 3: 3: 2. The physicochemical properties of the hydrolysates obtained have been studied. The maximum content of calcium in terms of the mass fraction of moisture is 11.2%, that of phosphorus - 9.2%. The mass fraction of fat in terms of the mass fraction of moisture does not exceed 2.3%; the mass fraction of crude fiber does not exceed 0.9%. Thus, according to these indices, all enzymatic hydrolysates of the gut evisceration products correspond to necessary parameters. Only a 24-hour fermentative hydrolysate corresponds to the mass fraction of calcium and phosphorus in terms of the mass fraction of moisture. As for the mass fraction of protein (81.4%), recalculated for the mass fraction of moisture, none of the tested hydrolysates corresponds to the necessary norm for the production of feed additives, which indicates the need for cleaning and degreasing enzymatic hydrolysates of gut evaporation waste in order to increase the mass fraction of protein. The content of toxic elements, radionuclides, bacterial organisms in the tested enzymatic hydrolysates of evisceration of poultry does not exceed the normalized values in accordance with GOST 17536-82 "Animal feed fodder. Specifications».